Association between polyvascular atherosclerosis and estimated glomerular filtration rate in patients with ischaemic stroke: data analysis of the patients in the Chinese National Stroke Registry. (20th May 2015) - Meng, Xia; Chen, Yu; Jing, Jing; Zhao, Xingquan; Wang, Chunxue; Liu, Liping; Wang, Anxin; Pan, Yuesong; Li, Chao; Wang, Yilong
Abstract : Objectives: This study evaluated the prevalence of chronic kidney disease (CKD) in ischemic stroke (IS) patients with polyvascular disease (PolyVD) and analysed the relationship between PolyVD and estimated glomerular filtration rate (eGFR) in IS patients. Methods: Data from 9152 consecutive IS patients from the China National Stroke Registry were analysed. PolyVD was defined as patients with IS and coronary artery disease (CAD) and/or peripheral arterial disease (PAD). Chronic kidney disease was defined as eGFR < 60 mL/minute/1.73 m 2 .The prevalence of CKD in IS patients with PolyVD was calculated. Logistic regression was used to estimate the correlation between PolyVD and eGFR between the monovascular group (IS alone) and the PolyVD group after adjusting for age, current or previous smoking, moderate or heavy drinking, body mass index, hypertension, dyslipidemia, diabetes mellitus, atrial fibrillation, previous stroke, and National Institutes of Health Stroke Scale scores. Results: PolyVD was observed in 1387 of 9152 patients (15.16%). Among these patients, 1351 (14.76%) had CAD, 56 (0.61%) had PAD, and 20 (0.22%) had CAD and PAD in addition to IS. The prevalence of CKD in IS patients with PolyVD and IS alone was 29.56 and 16.28%, respectively ( P  < 0.0001). The PolyVD group had a significantly higher risk of lower eGFR (OR: 1.414, 95% CI: 1.202–1.665, P  < 0.0001) compared with patients with IS alone. Discussion: IS patients with PolyVD had a high prevalence of CKD, and PolyVD was independently associated with a low eGFR.